DESIGNING PUPPET-BASED ENGLISH LEARNING VIDEOS FOR FOURTH GRADERS: A NEEDS-DRIVEN DEVELOPMENT STUDY - Maya Fahrunnisa; Nesa Selvia Fransiska Nababan; Putri Zuhra Pratama; Anggraini Thesisia Saragih; Khairul Azmi Siagian (UIN Sumatera Utara, 2026)
English learning at the elementary level requires engaging instructional media to support vocabulary and speaking development. However, the systematic integration of needs analysis into puppet-based video design remains underexplored in Indonesian EFL contexts. This study aimed to develop a puppet-based English learning video for fourth-grade students and to evaluate its validity and feasibility through expert judgment. The study employed a Research and Development (R&D) design based on the Analysis, Design, and Development phases of the ADDIE model. Data were collected from 20 fourth-grade students and two English teachers using questionnaires grounded in needs analysis principles. The findings revealed that students prioritized speaking skills (55%), experienced difficulties in vocabulary retention, and preferred video-based (65%) and puppet-assisted (85%) learning media. Based on these findings, a seven-minute puppet-based instructional video entitled